2018
DOI: 10.1111/jac.12316
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms associated with tiller suppression under stagnant flooding in rice

Abstract: Stagnant flooding (SF) during vegetative growth triggers stem elongation usually at the cost of tiller production in rice, reducing grain yield. To explore physiological mechanisms associated with tillering suppression under SF, three contrasting genotypes (Swarna and Swarna‐Sub1, both sensitive and IRRI154, tolerant) were evaluated under standing water depths of 0, 5, 30 and 50 cm. SF significantly suppressed tiller formation but increased plant height, root biomass, shoot elongation (ratio of plant height be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…The number of panicles is affected by the number of tillers at the tillering stage (Ao et al, 2010). Previous studies indicate that tiller number will decline sharply during submergence (Kato et al, 2014;Zhu et al, 2019), and in our study, we also found that tiller number decreased greatly in the submergence treatment than compared to that in the control. Accordingly, the lower tiller numbers led to reduced panicle number at the maturity stage (Figure 1).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The number of panicles is affected by the number of tillers at the tillering stage (Ao et al, 2010). Previous studies indicate that tiller number will decline sharply during submergence (Kato et al, 2014;Zhu et al, 2019), and in our study, we also found that tiller number decreased greatly in the submergence treatment than compared to that in the control. Accordingly, the lower tiller numbers led to reduced panicle number at the maturity stage (Figure 1).…”
Section: Discussionsupporting
confidence: 75%
“…Numerous studies have indicated that leaf photosynthetic rates of submerged inbred rice will be reduced because light intensity and gas diffusion rates rapidly decline under water (Gautam et al, 2015;Zhu et al, 2019). Consequently, contents of non-structural carbohydrates (NSC) in rice stems and biomass accumulation are reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Foliar MDA concentration was recorded to evaluate oxidative damage in relation to lipid peroxidation accumulation as a response to salinity and inundation stress ( De Azevedo Neto et al . 2006 ; Zhu et al ., 2019 ). MDA was assayed following Buege and Aust (1978 ).…”
Section: Methodsmentioning
confidence: 99%
“…The experiments were repeated at least three times. The plant elongation rates were calculated using the technique of Zhu et al [28]. The plant elongation rate denotes the difference in the length of the plant's above-ground part before and after treatment.…”
Section: Seedlings Plant High Fresh Weight Dry Weight Chlorophyll Cmentioning
confidence: 99%